Level of Augmentative and Alternative Communication Knowledge and Skills among Special Education Teachers for Autistic Students in Primary School - Shuhada Abdul Ghani; Suziyani Mohamed (Journal of ICSAR, 2019)
Supplementary and replacement communication or augmentative and alternative communication (AAC) is needed to replace the voices of autistic pupils who have difficulty communicating throughout the learning and facilitating process (PdPC) in the classroom. The teacher’s proficiency in communication skills can enhance and develop positive learning behaviours of autistic pupils throughout the learning process. This research aims to identify augmentative and alternative communication skills among special education teachers for autistic pupils in the classroom. A total of 73 special education teachers throughout Malaysia were selected as the respondents for thy research. The data obtained in the form of percentage shows the knowledge and skills of teachers in implementing AAC. Overall, this research shows that the level of knowledge and skills of teachers in implementing AAC in the classroom is still moderate and requires training.